“Mind the Leadership Gap!”: A Call to Action for the Future Research Agenda - Murphy, Liam; Turnbull, Helen (GILE Journal of Skills Development, 2023)
The coronavirus pandemic has acted as a catalyst for organisational change, disrupting historic ways of working, and spearheading organisations towards the next evolution of their working environments. In the aftermath of the largest concurrent work from home experiment in the world, organisations are coming to grips with the new policies and practices they need to implement to remain competitive. But there is one crucial stakeholder who continues to be left out in academic research, leaders. New questions now arise as to how we should remodel leadership in an increasingly remote world. What skills do leaders need to develop and how, in order to maintain employee wellbeing and manage the intergenerational divide? This paper presents a short synthesis of the challenges faced by leaders today specifically around remote team management but also in the context of a multigenerational workforce, alongside a summary of the research gaps we face in post-COVID literature. This paper concludes with the production of a future research agenda for scholars to close this gap, and to help organisations in building their leadership capability in the ‘new normal’.